APLIKASI DOA SEHARI-HARI ANAK ISLAM BERBASIS MOBILE PADA TPA AL-HIDAYAH SUKAJADI - khusnul khotimah; Nabila Umi Khoirunisa; Septiana Sari (LPPM Universitas Muhammadiyah Kotabumi, 2021)
Daily prayers are an integral part of a Muslim's life, but memorizing and learning these prayers can be a challenge for children. Currently, there is a lack of availability of daily prayer applications specifically designed for Muslim children, which provide interactive and engaging features for them. This research aims to design and develop a mobile-based daily prayer application for Muslim children that is suitable for the needs and characteristics of children at the Al-Hidayah Sukajadi Quran Education Park (TPA). This research utilizes a design and development approach. The application is expected to help children learn and memorize daily prayers interactively and enjoyable, while providing a deep understanding of the meaning and significance of each prayer